1979
DOI: 10.1080/00039896.1979.10667400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electric Arc Welding on Ventilatory Lung Function

Abstract: Respiratory symptoms, spirometry, forced expiratory flows, and the nitrogen closing volume test were studied in 119 welders and 90 controls, matched with respect to age, height, and smoking habits. Respiratory symptoms according to a questionnaire were more prevalent in the welders. No short-term changes of the measured variables during the day or week attributable to welding were found in twenty-one nonsmoking welders. Compared to the controls, closing volume and closing capacity (i. e., closing volume + resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
2

Year Published

1980
1980
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 8 publications
2
31
0
2
Order By: Relevance
“…Work-related symptoms were common in this study population, and work-related cough was found to be more frequent among the cussent welders than among the nonwelders. Although still a matter of controversy, chronic bronchitis is known to be associated with occupations involving exposure to dusts (15), and many studies have clearly documented an excess of these symptoms for current welders (13,14,(16)(17)(18)(19)(20) and sheet metal workers exposed to welding fumes (21).…”
Section: Discussionmentioning
confidence: 99%
“…Work-related symptoms were common in this study population, and work-related cough was found to be more frequent among the cussent welders than among the nonwelders. Although still a matter of controversy, chronic bronchitis is known to be associated with occupations involving exposure to dusts (15), and many studies have clearly documented an excess of these symptoms for current welders (13,14,(16)(17)(18)(19)(20) and sheet metal workers exposed to welding fumes (21).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of smokers varies between 37 and 56 Ofo in different groups of welders in Sweden (13,15,16,17). In different studies of the male population in Sweden the percentage of smokers has varied between 46 and 54 (8,18,24).…”
Section: Discussionmentioning
confidence: 99%
“…Stainless steel is an alloy which contains mainly iron but also chromium (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and nickel (0.5-20 Ofo). The electrodes used contain about the same amount of chromium and nickel.…”
mentioning
confidence: 99%
“…Previous studies 13,14,15 have noted a variety of acute and chronic health problems associated with arc welding, which have not clearly been attributable to any single metal fume or gas exposure, but which may be related to the combined effects of different exposures created by arc welding. Some metal fumes and gases generated by welding are respiratory irritants, and symptoms of eye, nose, and throat irritation, as well as cough and phlegm production, have been reported by welders in association with their work shift.…”
Section: B Effects Of Arc Welding On Respiratory Symptoms and Lung Fmentioning
confidence: 99%
“…Based on these reviews, a NIOSH environmental sampling protocol was established to focus on the welding operations. Environmental monitoring was performed on February [14][15]1989. Results of the environmental monitoring were forwarded to the company and union officials on July 13,1989.…”
Section: Introductionmentioning
confidence: 99%